Peningkatan Kompetensi Pembuatan Kerah Rebah Menggunakan Model explicit instruction pada Siswa Kelas X-A Tata Busana di SMK Negeri 3 Metro Tahun Pelajaran 2017/2018 - Esti Rahayu (Citra Dharma Cindekia, 2022)
This study aims to improve the competence of making collars for students in class X-A Fashion Design at SMK Negeri 3 Metro using the Explicit Instruction model. This classroom action research (CAR) research uses the Kemmis and McTaggart spiral model, carried out in 2 cycles. Cycle stages include planning, action and observation, and reflection. The subjects of this study were students of class X Fashion Design at SMK Negeri 3 Metro, totaling 35 students for the 2018/2019 academic year. The method of data collection used the observation sheet for the implementation of the Explicit Instruction model, the performance test sheet, and the performance sheet for making a laying collar. Proof of instrument validity uses content validity, reliability verification uses the method between raters with the Procentage Of Agreement level. The data analysis technique is descriptive quantitative. The results of this study were indicated by an increase in the percentage of students' complete learning outcomes, an increase from 33% pre-cycle, namely 12 students were declared complete, to 67% students with 24 students in the first cycle, and the second cycle increased to 100%, namely 35 students. This proves that the Explicit Instruction learning model can improve the competence of making a collapsing collar for class X-A Fashion Design at SMK Negeri 3 Metro.